MEMBANGUN TEOLOGI LOKAL: Akulturasi Nilai-Nilai Kristiani melalui Pemaknaan Tari Moyo dalam Masyarakat Nias - Larosa, Setiaman (Sekolah Tinggi Agama Kristen Luwuk Banggai, 2024)
This study stems from the need to understand the potential of Moyo Dance as a medium for acculturating Christian values within the cultural context of the Nias community. Moyo Dance, with its cultural elements such as movements, song lyrics, costumes, musical instruments, and folklore, reflects universal values that resonate with the teachings of the Gospel. This research aims to reinterpret these elements in the light of contextual theology. The method employed is library research, with data collected through literature reviews of books, journal articles, and relevant documents. The data were analyzed using a contextual hermeneutic approach, specifically the anthropological model of Stephen B. Bevans. The findings reveal that cultural elements in Moyo Dance can be integrated with Christian values such as love, sacrifice, courage, and joy, creating harmony between faith and local culture. These findings underscore the importance of contextual theology in fostering relevant and authentic spirituality.